New findings of Eurycercus Baird, 1843 (Cladocera: Anomopoda) in the Eastern Palaearctic - Bekker, Eugeniya I.; Novichkova, Anna A.; Kotov, Alexey A. (Zootaxa, 2014)
Information on the cladocerans of Eastern Palaerctic is limited, and remote islands of Arctic and Subarctic in this region are among inadequately studied territories, i.e. due to a very limited access to them. “Nearctic” Eurycercus longirostris is reported here for the first time from Bering Island and Wrangel Island. Also E. macracanthus is found to be common in Kamchatka Peninsula, while previously only a single population was known. We concluded that the Beringian land bridge played, together with glaciation in North America, important role in the evolutionary history of Eurycercus (Eurycercus), as it was earlier demonstrated for other cladocerans and other animals.